The Economics of Winning Hearts and Minds : Programming Recovery in Eastern Ukraine - World Bank (World Bank, Washington, DC, 2021)
Since 2014, the armed conflict in Ukraine’s eastern provinces (oblasts) of Donetsk and Luhansk has dealt a heavy blow to people’s lives. The conflict has magnified the long-standing problems and created new ones. This study shows that scaling up efforts in the government-controlled areas (GCAs) of Donbas is desirable despite the subdued productivity in the region. This study recommends a decision tree approach to programming recovery in Donbas. Given the looming uncertainties and scenario-sensitivity of optimal policies, the recovery strategy should distinguish contingent policies from no-regret policies. Contingent policies change between the status quo and the reintegration scenarios, and they include interventions to mitigate conflict-related risks, risk-related transfers to address skill-shortages in GCAs, and investments for a contingent infrastructure strategy. By comparison, no-regret policies are desirable regardless of the conflict dynamics. They include the reforms to eliminate regulatory burdens and corruption; policies to open up the housing market; investments to modernize education for jobs and target low-hanging fruits in infrastructure; and efforts to produce better data to address knowledge gaps.